2009
DOI: 10.1007/s11255-008-9520-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sodium bicarbonate infusion versus normal saline infusion and its combination with oral acetazolamide for prevention of contrast-induced nephropathy: a randomized, double-blind trial

Abstract: It seems that both Bi and AZ reduce the risk of CIN-related AKI, and close monitoring of serum potassium is needed during bicarbonate infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 33 publications
2
28
1
1
Order By: Relevance
“…Recent studies focused on the comparative effectiveness of IV sodium bicarbonate (bicarbonate) and IV sodium chloride (saline) based on the hypothesis that alkalinization of tubular fluid with bicarbonate will decrease the generation of injurious reactive oxygen species. Several trials suggested bicarbonate to be more effective than saline (5)(6)(7)(8)(9)(10)(11)(12), whereas others reported no difference (13)(14)(15)(16)(17)(18)(19)(20)(21). A second preventive intervention that has received substantial attention is the administration of N-acetylcysteine (NAC), an antioxidant with vasodilatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focused on the comparative effectiveness of IV sodium bicarbonate (bicarbonate) and IV sodium chloride (saline) based on the hypothesis that alkalinization of tubular fluid with bicarbonate will decrease the generation of injurious reactive oxygen species. Several trials suggested bicarbonate to be more effective than saline (5)(6)(7)(8)(9)(10)(11)(12), whereas others reported no difference (13)(14)(15)(16)(17)(18)(19)(20)(21). A second preventive intervention that has received substantial attention is the administration of N-acetylcysteine (NAC), an antioxidant with vasodilatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…(37) Two subsequent RCTs by Recio-Mayoral et al in 2007 and Pakfetrat et al in 2009 compared the effect of a single bolus of NaHCO 3 before coronary angiography or PCI; both studies showed a significant reduction of CIN in the group treated with the NaHCO 3 bolus. (38,39) One meta-analysis involving a total of 1,734 patients showed that NaHCO 3 is superior to NaCl alone in the prevention of CIN in patients with moderate to severe CKD. (40) However, a study of 353 patients undergoing coronary angiography (MEENA trial) showed no benefit of sodium bicarbonate over normal saline in preventing CIN.…”
Section: 9% Of Normal Salinementioning
confidence: 99%
“…21, 25 Eleven authors used a combination of a 0.5 mg/dl absolute creatinine increase or a relative increase of 25%. 12-17,20,26-29 One study regarded an absolute increase of creatinine of 1.5 mg/dl or 25% relative decrease of estimated glomerular filtration rate (eGFR) 30 and Brar et al 31 used a change in GFR as the primary endpoint and a change in creatinine as a secondary definition of CI-AKI.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%